Prevalência de anticorpos contra arbovírus da família Bunyaviridae em búfalos de água - CASSEB, Alexandre Rosário (Universidade Federal do Pará, 2017)
The State of Pará comprises 26% of Brazilian Amazon region where a large diversity of arboviruses has been described. This study sought to assess the prevalence and distribution of haemagglutination-inhibition antibodies against antigens of nine different types of arbovirus of the Bunyaviridae family, where eight were Orthobunyavirus: Guaroa virus, Maguari virus, Tacaiuma virus, Utinga virus, Belem virus, Caraparu virus, Oropouche virus and Catu virus, and one Phlebovirus: Icoaraci virus in sera samples of water buffaloes in Pará State, Brazil. For all Arboviruses investigated there were antibodies, with the exception of Belem virus. Antibodies to Maguari viruswere more prevalent (7.33%). The water buffaloes of the present study showed variable levels of antibodies in monotypic and heterotypic reactions that may indicate there are movements from most bunyavirus studied in domestic buffaloes in the state of Pará, and the Maguari virus presents the largest circulation. Therefore, further studies are needed to investigate the role of water buffalo in the maintenance and dispersal of arboviruses, as well as whether these viruses can cause disease in that species, especially in cases of birth defects and abortions.